Diversity Development: Studies from Local Wisdom of Dayak in the Border Community of Indonesia-Malaysia - Nikodemus Niko (Jurnal Empirika, 2019)
Dayak ethnic life can not see in isolation with ecological conditions; that is where they live. Philosophy of life depends on the nature of the Dayak community, because without the natural result will be disrupted livelihoods for local people. In the Indonesia-Malaysia border region, small communities dwelt Dayaks and form local wisdom. In this paper, look the part of local wisdom of the Dayak community as an adhesive diversity in the border region. This paper uses a descriptive qualitative approach, where data derived from primary data and secondary data. Data obtained by observation and interviews, then the data is processed into the descriptions. The findings in this paper describe the life of the local Dayak communities in the border region and its interaction with the community in Malaysia. Then, woven splint, which is the local craft community, into the value of the adhesive between Dayak communities in the border region.